# Yahoo Web Search

1. ### Integral of 1 /( 1 + tanθ)?

∫ [ 1 /( 1 + tanθ)] dθ = let tanθ = t θ = arctan t dθ = [ 1 /(t² + 1 )] dt substituting, you have... = 0 | B + C = 0 | A + C = 1 | A = - B | C = - B | - B...

1 Answers · Science & Mathematics · 01/05/2009

2. ### Integrate (x^( 1 /2))/(x^( 1 /3)+ 1 )?

∫ {x^( 1 /2) /[x^( 1 /3) + 1 ]} dx = in such cases...in this case LCD = 6, thus let x^( 1 /6) = u → x = u^6 → dx = 6u^5 du x^( 1 ...integrand: 6 ∫ (u^6 - u^4 + u^2 - 1 ) du + 6 ∫ [ 1 /(u^2 + 1 )] du = break it up into: 6 ∫ u...

4 Answers · Science & Mathematics · 02/10/2008

3. ### Anti-derivative of √(2/(( 1 -u^2 ) )+ 1 /( 1 -u)^2 + 1 /( 1 +u)^2 )?

Hello, ∫ √{[2 /( 1 - u²)] + [ 1 /( 1 - u)²] + [ 1 /( 1 + u)²]} du = let's rearrange... 1 /( 1 - u)]² + [ 1 /( 1 + u)]²} du = ∫ √{ {2 /[( 1 + u)( 1 - u)]} + [ 1 /( 1 - u)]² + [ 1 /( 1 + u)]²} du = ∫ √{[ 1 /( 1 + u)]² + 2 [ 1 ...

1 Answers · Science & Mathematics · 06/10/2016

4. ### Integral of ∫ 1 /( 1 + tanθ).dθ?

∫ [ 1 /( 1 + tanθ)] dθ = let tanθ = t θ = arctan t dθ = [ 1 /(t² + 1 )] dt substituting, you have... = 0 | B + C = 0 | A + C = 1 | A = - B | C = - B | - B...

2 Answers · Science & Mathematics · 01/05/2009

5. ### 1 . simplify -10 / 1 -2i?

1 . The complex conjugate of ( 1 - 2i) = ( 1 + 2i). So multiply by (( 1 + 2i)/( 1 + 2i)): (-10)/( 1 - 2i) = = (-10)/( 1 - 2i) * 1 ... both sides: (8 + 7x) = x² + 4x + 4 x² - 3x - 4 = 0 (x - 4)(x + 1 ) = 0 x = 4, - 1

4 Answers · Science & Mathematics · 21/02/2009

6. ### solving ( 1 /10) (x+8/ 1 ) - ( 1 /15)(x-5/ 1 ) = 1 / 1 ?

1 ) 1 /10(x + 8) - 1 /15(x - 5) = 1 / 1 <=> (x + 8)/10 - (x - 5)/15 = 1 <=> 3(x + 8) - 2(x - 5) = 30 <=> 3x + 24 - 2x + 10 = 30 <=> x = 30 - 24 - 10 <=> x = -4...

2 Answers · Science & Mathematics · 24/03/2011

7. ### Simplify Complex Fraction? algebra 1 ?

1 . 1 /x + 2/x- 1 over 4/x- 1 = [(x- 1 +2x)/x(x- 1 )] / [4/(x- 1 )] = = (3x- 1 ) / 4x >==========================< ANSWER 2. 3/x+ 1 + 1 /x over 2/x+ 1 + 3/x = [3x+x+ 1 )/x(x+ 1 )] / [2/(x+ 1 )]= = (4x+ 1 ) / 2x >...

3 Answers · Science & Mathematics · 11/03/2012

8. ### Integrate: 1 /( 1 -3x) + 1 /( 1 +3x)?

∫( 1 /( 1 -3x) + 1 /( 1 +3x)) dx = (- 1 /3)ln( 1 -3x) + ( 1 /3)ln( 1 +3x) + c = ln( 1 +3x)/3 - ln( 1 -3x)/3 + c = ln...you would do it. this is done using this rule: ∫ 1 /(ax+b) = ln(ax+b)/a and when subtracting logs - as...

1 Answers · Education & Reference · 26/07/2009

9. ### Ear stretching question?????????????!?!???!?!?~!!??!?!?!?!?!?!!? 1 ?

1 1 1 /16 1 1 /8 1 1 /4 1 5/16 1 3/8 1 1 /2 1 5/8 1 3/4 1 7/8 2 etc.

1 Answers · Beauty & Style · 19/11/2010

10. ### Need Help simplifying ( 1 - 1 /x^2)/( 1 + 1 /x)?

( 1 - 1 /x² ) / ( 1 + 1 /x ) ----> Multiply by x² / x² ( x²...gt; Take x as a common factor from the denominator ( x - 1 )( x + 1 ) / ( x )( x + 1 ) ----> ( x + 1 ) cancels ( x + 1 ) ( x - 1 ...

6 Answers · Science & Mathematics · 14/04/2013